Post-Soviet Russian Academia Struggles with the Past - Androushchak, Gregory; Yudkevich, Maria (International Higher Education, 2012)
Contemporary Russian higher education remains influenced by the Soviet past. This historical tradition in general makes change and improvement more difficult. A special problem is the tradition of state planning.